Assessing digital competence and its impact on academic performance: insights from Universiti Malaysia Sarawak undergraduates - Victor, Ajibol Omoniyi; Ujir, Hamimah (Intelektual Pustaka Media Utama, 2025)
Information and communication technology (ICT) has become an essential part of the daily lives of tertiary students. However, research into assessing digital competency and its effects on academic performance is still limited. This paper explores students’ needs for digital competence, the impact of digital access on academic performance, and the relationship between digital competence and educational success, focusing on undergraduates at Universiti Malaysia Sarawak (UNIMAS). Using a model with 64 measurement items and nine variables, the study identifies significant correlations between information and data literacy (IDL), safety and security (SS), and problem-solving (PS) proficiency with digital competence. Conversely, communication and collaboration (CC) and digital content creation (DCC) show statistically insignificant correlations. Additionally, while digital resource availability has a minor inverse correlation, digital usage is significantly and positively related to digital competence. The findings suggest that digital competence strongly predicts academic performance and that most undergraduates exhibit advanced proficiency in essential digital skills. This research highlights the crucial role of digital competence in enhancing educational outcomes and offers insights into key competencies linked to digital effectiveness.